Clinical outcome of fetal uropathy. Issue 8 (August 1988) - Madarikan, B A; Hayward, C; Roberts, G M; Lari, J
Abstract : Thirty seven infants (27 boys and 10 girls) whose uropathy had been diagnosed antenatally were reviewed at a mean age of 24.4 months. Antenatal ultrasonography was found to be an accurate detector of renal disease, as uropathy was subsequently confirmed in 33 of the 37 infants (89%). A smaller proportion of patients required operations than in other series reported. Shortly after birth the kidney undergoes physiological adjustments and investigation may be carried out too soon. It should be delayed, especially if the infant is well. The timing of postnatal ultrasonography is important and the advice of a paediatric urologist should be sought before investigations are carried out.